Is Global Competitiveness Speeding Up the Growth in the EU? A Panel Data Analyis - Neagu, Olimpia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
The paper documents the impact of global competitiveness on economic growth in the EU Member States. In a panel data approach, for a time span of 10 years (20082017), a validated influence of Global Competitiveness Index on annual rate of GDP in the EU countries was found. The impact is higher in the group of Eastern and Central European countries (ECE) than in the Western European (well developed) countries, as well as at European economy level.